2016
DOI: 10.1590/2317-1782/20162014082
|View full text |Cite
|
Sign up to set email alerts
|

Influência da hipermobilidade articular generalizada sobre a articulação temporomandibular e a oclusão dentária: estudo transversal

Abstract: RESUMO Objetivo Avaliar a oclusão dentária e a articulação temporomandibular de mulheres com e sem hipermobilidade articular generalizada. Método A hipermobilidade foi avaliada pelo Escore de Beighton, e as voluntárias foram distribuídas, conforme o escore obtido, em dois grupos: com e sem hipermobilidade. A articulação temporomandibular foi avaliada por meio do instrumento Critérios de Diagnóstico para Pesquisa de Desordens Temporomandibulares, e a avaliação oclusal compreendeu a classificação de Angle, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
(38 reference statements)
1
2
0
2
Order By: Relevance
“…This would suggest that patients with TMJ disease, such as DD, would also be classified with GJH to a greater extent compared to a normal population. This has been shown in a study by Hirsch et al but refuted by others [ 7 , 16 , 30 ]. In the current study as many as 25% had GJH out of all patients attending the department with the diagnoses DDwR, DDwoR, DJD, or CIA, and with indications for surgery.…”
Section: Discussionsupporting
confidence: 68%
“…This would suggest that patients with TMJ disease, such as DD, would also be classified with GJH to a greater extent compared to a normal population. This has been shown in a study by Hirsch et al but refuted by others [ 7 , 16 , 30 ]. In the current study as many as 25% had GJH out of all patients attending the department with the diagnoses DDwR, DDwoR, DJD, or CIA, and with indications for surgery.…”
Section: Discussionsupporting
confidence: 68%
“…19,20 Chiodelli et al emphasized the need for a more thorough observation of TMD prevalence in HJS bearers, possibly using larger cohorts. 21 Their study concluded that TMJ and preauricular pain were significantly more common in HJS patients. 21 According to Kavuncu et al, up to 79.7% of TMD patients had HJS, 22 with similar results obtained by Pasinato et al (64.71%).…”
Section: Discussionmentioning
confidence: 98%
“…21 Their study concluded that TMJ and preauricular pain were significantly more common in HJS patients. 21 According to Kavuncu et al, up to 79.7% of TMD patients had HJS, 22 with similar results obtained by Pasinato et al (64.71%). 23 Additionally, the latter group of authors described a higher percentage of myofascial pain without mouth-opening restrictions in HJS participants (81.82%) as compared to nonhypermobile controls (58.33%).…”
Section: Discussionmentioning
confidence: 98%
“…Tanto a odontologia quanto os fonoaudiólogos são responsáveis pela classificação das oclusões dentárias. Essa classificação é baseada em estudos publicados pelos principais cientistas da área, como o apresentado por Angle dividido em três estágios (Chiodelli et al, 2016). O primeiro estágio foi considerado normal, usando a cúspide mesiovestibular do primeiro molar superior e o sulco mesiovestibular do primeiro molar inferior como ponto de vista (harmonia entre maxila e mandíbula), mas na segunda classificação temos a cúspide distovestibular do primeiro molar superior ocluindo no sulco mesiovesvtibular do primeiro molar inferior, essa classe apresenta possíveis alterações, como maxilar avançado ou maxilar recuado, palato estreito, contração mental, ausência de selamento labial, disfunção temporomandibular (DTM) e alterações em alguns fonemas.…”
Section: Discussionunclassified